Distinct cortical thickness correlates of early life trauma exposure and posttraumatic stress disorder are shared among adolescent and adult females with interpersonal violence exposure - Ross, Marisa C. (Neuropsychopharmacology, 2020)
Early life trauma (ELT) exposure and posttraumatic stress disorder (PTSD) both affect neural structure, which predicts a variety of mental health concerns throughout the lifespan and may present differently between adolescents and adults. However, few studies have identified the relationship between ELT, PTSD, development, and brain structure using cortical thickness (CT). CT may reveal previously obscured alterations that are potentially clinically relevant and, furthermore, could identify specific structural correlates distinct to ELT from PTSD. Two hundred and fifty-three female adolescent and adult survivors of interpersonal violence and non-trauma-exposed demographically matched controls underwent structural MRI at two different sites. Images were processed and CT was estimated using FreeSurfer. Vertex-wise linear model tests were conducted across the cortical surface to investigate whether PTSD and ELT exposure uniquely affect CT, controlling for scanner site. Planned follow-up tests included second-level analyses of clinical symptoms for CT clusters that were significantly related to PTSD or ELT. CT in the middle cingulate cortex was inversely related to ELT in both age groups, such that individuals with more ELT demonstrated less CT in this region. Additionally, CT was significantly greater in the bilateral intraparietal sulcus and left angular gyrus in both adolescents and adults with PTSD. Furthermore, CT in these clusters was also significantly related to clinical symptom severity in the adult PTSD group. This study provides evidence for distinct CT correlates of ELT and PTSD that are present across adolescents and adults, suggesting consistent markers related to ELT and PTSD on gray matter structure in trauma-exposed individuals.